2010
DOI: 10.3989/mc.2010.57010
|View full text |Cite
|
Sign up to set email alerts
|

Modelos estructurales del empaquetamiento aleatorio de partículas esféricas de Tobermorita: una aproximación computacional sencilla

Abstract: RESUMENEn este trabajo y con el objetivo de conjugar el punto de vista atomístico y coloidal, presentamos un método computacional Monte Carlo que reproduce el empaquetamiento coloidal de nano-partículas esféricas cristalinas de tipo Tobermorita. Variando los parámetros computacionales de empaquetamiento diferentes estructuras tipo Low Density (LD) C-S-H y High Density (HD) C-S-H han sido creadas. Posteriormente, las estructuras resultantes de nuestros experimentos computacionales han sido analizadas en término… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Finalmente, nos gustaría remarcar el potencial de los métodos de simulación atomísticos como fuente de información para modelizar la pasta de cemento a escalas mayores [49][50][51][52], y alcanzar una descripción multiescalar del material y sus propiedades. These trends of elastic constants and densities have been compared with those of the cementitious CSH gel and synthetic CSH type I.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Finalmente, nos gustaría remarcar el potencial de los métodos de simulación atomísticos como fuente de información para modelizar la pasta de cemento a escalas mayores [49][50][51][52], y alcanzar una descripción multiescalar del material y sus propiedades. These trends of elastic constants and densities have been compared with those of the cementitious CSH gel and synthetic CSH type I.…”
Section: Discussionunclassified
“…Finally, we would like to stress the potential that atomistic simulation methods have, as a source of information for modelling the the cement paste at larger scales [49][50][51][52], and achieve a multi-scalar description of the material and its properties.…”
Section: Agradecimientosmentioning
confidence: 99%
“…This simplification constitutes a significant weakness of the model. In fact, the computational study published in 2010 by González-Teresa et al [48] based on Monte Carlo simulations of the packing arrangements, suggested that the computational counterpart of the ''experimentally inaccessible HD C-S-H'' could also contribute to the specific surface area measurements. Their computational model provided significant convergence with the LD C-S-H SSA measured by SANS [71].…”
Section: Classification Of C-s-h With Respect To Packing Densitymentioning
confidence: 96%
“…Manzano et al [46] 2007 Two different growth mechanisms Jennite, tobermorite Ab-initio calculations at the Hartree Fock (HF) level Dolado et al [47] 2007 Analysis of polymerisation of silicic acids in a calcium rich environment Jennite, tobermorite Molecular dynamics method by Feuston and Garofalini Pellenq et al [12] 2008 Iono-covalent forces between individual C-S-H layers or C-S-H layer stacks Nanocrystals Ab-initio, molecular dynamics and energy minimisation techniques Skinner et al [5] 2010 Analysis on synthetic C-S-H and hydrated C 3 Sshort silicate chains due to nanocrystallinity Structure close to Hamid's 1.1 nm tobermorite -evidence of nanocrystallinity Pair distribution function, Monte Carlo, Fourier transformations on XRD results González-Teresa et al [48] 2010 Inaccessibility of HD by N 2 and HD also contributes to the SSA-smaller globules…”
Section: Researchersmentioning
confidence: 98%
“…The size, shape or crystallographic nature and water content of the basic building blocks, and their arrangements forming hierarchical fractal structures, are currently the focus of research efforts, both experimentally [19][20][21] and computationally [14,22]. Tobermorite or jennite are being proposed as structural references for the basic building blocks [11,23].…”
Section: Calcium Silicate Hydrate (C-s-h)mentioning
confidence: 99%